ESG Disclosure and Firm Value in Emerging Markets: A PRISMA-Guided Systematic Review with Bibliometric Analysis - Raudah Nera Penalo; Anang Muftiadi; Erna Maulina (Journal of Social Work and Science Education, 2026)
This study examines the relationship between environmental, social, and governance (ESG) disclosure and firm value in emerging markets through a PRISMA-guided systematic literature review and bibliometric analysis. A systematic search was conducted on 15 May 2026 using Google Scholar, Scopus, and Web of Science for studies published between 2020 and 2025. The search identified 13,700 records. The review included peer-reviewed empirical articles published in English or Indonesian, indexed in Scopus, Web of Science, or Sinta, and focused on ESG or corporate social responsibility disclosure and firm value or financial performance in emerging markets. After identification, screening, eligibility assessment, and full-text evaluation, 22 studies were included in the final synthesis. Bibliometric mapping was conducted using VOSviewer through keyword co-occurrence and co-citation analyses. The findings show that 18 of the 22 studies, or 82%, reported a statistically significant positive relationship between ESG disclosure and firm value. The environmental dimension showed the strongest and most consistent association with firm value, while the effects of social and governance disclosure varied across institutional and market contexts. Firm size, institutional ownership, leverage, regulatory quality, and economic sustainability emerged as important moderating or mediating factors. The bibliometric analysis identified three main research clusters: ESG reporting and disclosure mechanisms, firm value and financial performance measures, and corporate governance and stakeholder-related factors. The review also identifies methodological and geographical gaps, particularly the limited use of causal research designs and the underrepresentation of African and Latin American emerging markets. These findings provide relevant implications for corporate managers, investors, regulators, and future ESG researchers.